2018
DOI: 10.1001/jamacardio.2018.2936
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Safety and Clinical Outcomes of a Transcatheter Interatrial Shunt Device for the Treatment of Heart Failure With Preserved Ejection Fraction in the Reduce Elevated Left Atrial Pressure in Patients With Heart Failure (REDUCE LAP-HF I) Trial

Abstract: ClinicalTrials.gov identifier: NCT02600234.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 28 publications
3
99
0
7
Order By: Relevance
“…Analogously, the REDUCE LAP-HF I trial on a total of 64 patients recorded a reduction in left-atrial pressure during exercise with improvement in functional capacity and QOL after shunt implantation [143]. The latest 1-year results of REDUCE LAP-HF I showed no significant differences in major adverse cardiac, cerebrovascular, or renal events compared to patients who underwent sham procedure, suggesting this method to be safe [144]. In the future, the REDUCE-LAP-HF II trial, which focuses on clinical outcomes, will hopefully take up from these positive results (NCT03088033).…”
Section: Atrial Shunt Devicementioning
confidence: 95%
“…Analogously, the REDUCE LAP-HF I trial on a total of 64 patients recorded a reduction in left-atrial pressure during exercise with improvement in functional capacity and QOL after shunt implantation [143]. The latest 1-year results of REDUCE LAP-HF I showed no significant differences in major adverse cardiac, cerebrovascular, or renal events compared to patients who underwent sham procedure, suggesting this method to be safe [144]. In the future, the REDUCE-LAP-HF II trial, which focuses on clinical outcomes, will hopefully take up from these positive results (NCT03088033).…”
Section: Atrial Shunt Devicementioning
confidence: 95%
“…On the other hand, SAX LAEF is an alternative if long axis images are degraded by artefact. Our findings are also important since LAEF represents a potential therapeutic target in HFpEF [8] where there are currently no effective therapies [9] and may also act as a trial endpoint [10].…”
Section: Discussionmentioning
confidence: 92%
“…The fact that Schueler et al reported patients with persistent iASDs had worse outcomes may argue against iASDs being beneficial long term in patients without diastolic heart failure or with systolic heart failure . There is an ongoing randomized clinical trial studying creation of an iatrogenic ASD in patients with heart failure with preserved ejection fraction to relieve elevated left atrial pressure; however, that trial has important exclusion criteria (including right ventricular dysfunction, pulmonary hypertension, prior stroke, and prior pulmonary embolism) and is thus not applicable to our patient population …”
Section: Discussionmentioning
confidence: 98%
“…5 There is an ongoing randomized clinical trial studying creation of an iatrogenic ASD in patients with heart failure with preserved ejection fraction to relieve elevated left atrial pressure; however, that trial has important exclusion criteria (including right ventricular dysfunction, pulmonary hypertension, prior stroke, and prior pulmonary embolism) and is thus not applicable to our patient population. 20 Certain limitations should be considered. This is an observational study, and thus, definitive conclusions regarding outcomes cannot be drawn as there was some variability in the characteristics of the patients in the two arms of the study.…”
Section: Discussionmentioning
confidence: 99%